Perspektif IPA: Hubungan Self Efficacy dan Motivasi terhadap Kemajuan Karier Akademik Dosen - Chandra, Rodi; Disajati, Melani; Kurniawan, Romi (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to analyze the influence of self-efficacy and motivation on lecturers' academic career progress, particularly in terms of functional promotion and scientific publications. Using a quantitative approach, data were collected from lecturers in various universities. The results of the analysis show that self-efficacy and motivation play a significant role in increasing lecturer productivity, both in achieving functional positions and scientific publications in reputable journals. Lecturers who have high self-efficacy are more confident in facing research challenges, while motivation is the main driver to achieve academic goals. The implications of these findings suggest the importance of institutional support in improving both factors to encourage lecturers' career development. The study also identified limitations related to external factors such as cost and access to publications that may affect research outcomes. Therefore, recommendations are made to improve support for lecturers in terms of training and better access to research resources.